Soft Kompetensi Pustakawan Dalam Mencegah Tindakan Bibliocrime - Nia Sopariah; Rosiana Nurwa Indah; Tansah Rahmatullah; Rifqi Zaeni Achmad Syam (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2023)
The book data registered was 541 copies, including 503 copies of books that were slightly damaged and 38 copies of books that were heavily damaged due to human factors in the adult reading room. damage to books due to human factors, often read by users so that the books are damaged or scratched. This research discusses the prevention of Bibliocrime and the competence of librarians in preventing Bibliocrime. The aim of this research is to determine the soft competence of librarians in terms of achievements and actions, customer service orientation, self-control in physical, electronic and procedural forms to prevent bibliocrime in the Regional Library and Archives Service of West Java Province. The research method in this research is that the researcher uses the constructivism paradigm in his research paradigm. The method used uses a qualitative approach with descriptive methods. The theory used uses Spencer & Spencer. The results of the research show that librarians at the West Java Province Regional Library and Archives Service already have librarian soft competence in preventing bibliocrime in library collections in physical, electronic and procedural forms. However, the librarian's soft competence when viewed from the aspects of achievement and action, customer service orientation, and self-control is still at a low level. increasing the soft competence of librarians in dealing with bibliocrime by conducting comparative studies, attending seminars and holding FGDs on topics related to bibliocrime.